Pengaruh Harga, Cita Rasa, dan Kualitas Pelayanan terhadap Kepuasan Konsumen di Caffe Tandalan Blitar - Yessy Siscilia Saputra; Moch. Saleh Udin; Heru Sutapa (Jurnal Riset dan Inovasi Manajemen, 2023)
The purpose of this research is to determine the variables price (X1), taste (X2) and service quality (X3) on consumer satisfaction (Y) at Caffe Tandalan Blitar. This type of research is quantitative research. The data collection techniques used are primary data and secondary data. Sample selection used Accidental Sampling, the number of samples in this study was 187 respondents at Caffe Tandalan Blitar. This research data was obtained from questionnaires, interviews and literature studies. The analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test and Coefficient of Determination Test. The research results showed that the multiple linear regression equation Y= - 1.739 + 0.320 T test results: The taste variable has a partially significant effect on consumer satisfaction with a sig result of 0.000 <0.05. t test results, the service quality variable has a partially significant effect on consumer satisfaction with a sig result of 0.000 < 0.05. The F test results obtained Fcount results with a significance value of 0.000 < 0.05. From the results of the analysis it can be concluded that price, taste and service quality have a simultaneous and significant effect on consumer satisfaction.